Discussion on hot spots of flatfoot deformity treatment - HONG Hao; YU Guangrong (Guangxi Yike Daxue xuebao)
Flatfoot is a deformity disease caused by congenital or acquired factors that lead to abnormal bone morphology and alignment of the foot, as well as inflammation or damage of tendons and ligaments, resulting in the collapse of the arch of the foot. Asymptomatic patients with flatfoot may not require intervention. For symptomatic patients, conservative treatment is recommended first, and patients who have no effect after more than 3 months of conservative treatment can be treated with surgery. Different treatment strategies are adopted for flatfoot in adults and children.